Study on the supply respnose and marketing of natural rubber in Kerala - Viju Ipe C (Department of Agricultural Economics, College of Horticulture, 1986)
The present study on supply response and marketing of natural rubber in Kerala developed estimates of short-term and long-term supply response of rubber to price changes and analysed the structure and performance of the rubber market in Kerala. To analyse the supply response time-series data on area, production, productivity and prices of natural rubber published by the Rubber Board were used. The trend analysis showed that over the period of 31 years from 1953-’54 to 1983-’84, the total area, tappable area, production, productivity and prices of natural rubber showed positive and appreciable growth rates. In the case of tappable area, production and productivity, simple and compound growth rate during the period after 1960-’61 were greater than during the period prior to 1960-’61. Similarly in the case of price of natural rubber the growth rates during the period after 1976-’77 were greater than that during the period prior to 1976-’77. Econometric analysis of the short-run supply response showed that the response to one year lagged price was positive though not significant with an elasticity of 0.0468. The response of average yields to current price was negative but not significant. The variables considered explained over 94 per cent of the total variation in the average yield of rubber. The analysis revealed the existence of a significant time trend indicative of the technological changes in rubber production. The elasticity with respect to the current price was -0.1247 and that with respect to the lagged price of rubber relative to that of coconut was -0.1135. In the analysis of long-term supply response, the producer expectations derived by the declining geometric lag weighted specification and moving average models, were tried but the latter performed better. The variables considered explained over 80 per cent of the total variation in the new planted area. The response of new-planted area to the expected price of rubber was positive with an elasticity of 0.5492. The elasticity with respect to the expected price of coconut was -0.4309. Similarly the response of newplanted area to the expected price of rubber relative to that of coconut price was positive with an elasticity of 0.3430. The analysis of market structure revealed six important channels in the sheet rubber market. The analysis of market concentration point to the possibility of decreasing competition among the dealers with larger volumes and thus the possibility of increasing share of the total market for rubber. This, however, does not seem to have appreciably affected the market margins, and the element of competition is still perceptible. The gross marketing margin worked out to Rs.78.95 per quintal of sheet rubber and the marketing costs incurred by all the intermediaries was Rs.28.82 per quintal. The net marketing margin was Rs.50.13 per quintal. The price spread between the primary dealer and the producer was Rs.20.14 per quintal and that between the primary dealer and the secondary dealer was Rs.58.76 per quintal. The marketing costs incurred by the primary dealer and the secondary dealer were Rs.9.94 and Rs.18.87 per quintal of sheet rubber respectively. The producer’s share in the manufacturers rupee worked out to 95.27 per cent. The analysis of progress made by the co-operative societies dealing in rubber in terms of their number and total quantity of sheet rubber marketed showed that they declined over the period from 1971-’72 to 1979-’80.